Exercise Capacity and Ventricular Remodeling After Transcatheter Ventricular Septal Defect Closure in Asymptomatic or Minimally Symptomatic Adolescents and Adults. (June 2020) - Chen, Chun-An; Wang, Jou-Kou; Lin, Ming-Tai; Chiu, Hsin-Hui; Hsu, Jui-Yu; Lin, Shu-Man; Chang, Ya-Mei; Chiu, Shuenn-Nan; Lu, Chun-Wei; Wu, Mei-Hwan; Yang, Ming-Chun
Abstract : Background: Transcatheter ventricular septal defect (VSD) closure is a safe and efficacious alternative to surgery. However, its benefits in asymptomatic or minimally symptomatic patients remain unknown. Methods: Sixty patients with VSD aged 12 to 60 years underwent cardiopulmonary exercise test and echocardiography 1 day before transcatheter VSD closure and 6 months after intervention (closure group). Thirty patients who did not receive the intervention underwent the same evaluations over 6 months (observation group). Results: No significant change in exercise function was observed after VSD closure, except for increased peak oxygen (O2 ) pulse (absolute increase: 0.4±1.4 mL/beat). Left ventricular end-diastolic dimension and mitral peak early filling velocity-to-early diastolic annular velocity ratio decreased (absolute decrease: 0.3±0.6 cm and 0.7±1.9, respectively). Despite unchanged overall peak O2 consumption, 33% of closure group patients exhibited clinically significant improvements in peak O2 consumption (>10% increase relative to baseline). This was not related to the pulmonary flow-to-systemic flow ratio or baseline exercise capacity. By contrast, all exercise function parameters deteriorated significantly in the observation group. Subgroup analysis revealed that patients with a baseline left ventricular end-diastolic dimension Z score of >2 exhibited a significantly greater improvement in peak O2 consumption, peak O2 pulse, and oxygen uptake efficiency slope than did the observation group. Conclusions: Compared with conservative management, transcatheter VSD closure prevents deterioration in exercise capacity and promotes left ventricular reverse remodeling in asymptomatic or minimally symptomatic patients. These benefits are most prominent in patients whose left ventricular end-diastolic dimension Z score before intervention is >2, irrespective of baseline peak O2 consumption and pulmonary flow/systemic flow ratio. Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT03127748.